Teknik Pembenihan Ikan Maskoki (Carassius Auratus) Di Balai Benih Ikan Ciganjur - Nabila, Salwa (Jurnal Perikanan dan Kelautan, 2025)
Discusses goldfish (Carassius auratus) spawning techniques at the Ciganjur Fish Seed Center (BBI), Center for Fishery Product Inspection and Certification (PPISHP), DKI Jakarta Province. The aim is to understand spawning techniques and factors that influence their success. The methods used include observation, interviews, and active participation in the spawning process. The results show that goldfish hatchery includes preparation of spawning ponds, selection of broodstock, spawning, egg collection, hatching, larval rearing, and initial care. Egg productivity reached 4,510 eggs, with a fertilization rate of 83.6%, a hatching rate of 74.8%, and a survival rate of 10%. Pests and diseases encountered included dragonfly larvae and Argulus, which were controlled through direct removal, pond cleaning, and water quality management. Routine water quality monitoring and optimal pest and disease control are recommended to increase the success of goldfish hatchery.